A new species and a new record of Curcuma subgen. Curcuma (Zingiberaceae) from Northern Thailand - Surapon Saensouk; Thawatphong Boonma; Piyaporn Saensouk (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk S, Boonma T, Saensouk P. 2021. A new species and a new record of Curcuma subgen. Curcuma (Zingiberaceae) from Northern Thailand. Biodiversitas 22: 3617-3626. Recent fieldwork to study the species diversity of the Zingiberaceae family in Thailand and preparing a revision of the Curcuma genus for the Flora of Thailand, an undescribed species of Curcuma uses as traditional medicinal for more than two decades well known in the Thai vernacular name “Rang-Jued” was found, this vernacular name is also used to call the other two medicinal plants belonging to different families which are Thunbergia laurifolia Lindl. (Acanthaceae), and Crotalaria spectabilis Roth (Fabaceae), thus some villagers are named Curcuma rangjued as “Rang-Jued-Khamin” to communicate specifically identify species in order to use correct species for each utilization. While Thunbergia laurifolia was called "Rang-Jued-Thao", which "Thao" means "vine" refers to its habit and Crotalaria spectabilis was called "Rang-Jued-Ton" which "Ton" means "stem" refers to its erect stems. After comparing this undescribed species of Curcuma with its allies species, we found that this species did not match with any existing taxa, thus described with detailed illustrations, photographs, summaries for its distribution, ecology in the name of Curcuma rangjued Saensouk & Boonma and followed by a new record of C. cordata Wall. for Thailand which in the past has been determined as a synonym of C. petiolata Roxb. but now it is back to a recognized name once again. Both species in this study were found distributed in the northern region of Thailand and belong to Curcuma subgenus Curcuma, their description along with ecology, phenology, and a revised key to 28 species of Curcuma subgenus Curcuma in Thailand are also present for facilitating identification.